2019
DOI: 10.1115/1.4044054
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Human Tibia Modeled as a Functionally Graded Material

Abstract: Human tibia, the second largest bone in human body, is made of complex biological material having inhomogeneity and anisotropy in such a manner that makes it a functionally graded material. While analyses of human tibia assuming it to be made of different material regions have been attempted in past, functionally graded nature of the bone in the mechanical analysis has not been considered. This study highlights the importance of functional grading of material properties in capturing the correct stress distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This paper focuses on the bending stiffness of the tibia. According to CT scanning images ( Figure 1 a), the geometric properties of the cross section of the dense bone of the tibia change linearly, that is, it gradually decreases from the proximal end to the distal end [ 24 , 25 , 26 , 27 ]. Studies found that the second moment of area and inertia change linearly along the tibia.…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on the bending stiffness of the tibia. According to CT scanning images ( Figure 1 a), the geometric properties of the cross section of the dense bone of the tibia change linearly, that is, it gradually decreases from the proximal end to the distal end [ 24 , 25 , 26 , 27 ]. Studies found that the second moment of area and inertia change linearly along the tibia.…”
Section: Introductionmentioning
confidence: 99%